2016
DOI: 10.4238/gmr.15038664
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic and expression analysis of the OMT gene family in Pyrus bretschneideri cv. Dangshan Su

Abstract: ABSTRACT. With high nutritional value in its fruits, Dangshan Su pear has been widely cultivated in China. The stone cell content in fruits is a key factor affecting fruit quality in pear, and the formation of stone cells has been associated with lignin biosynthesis. O-Methyltransferase (OMT) is a key enzyme involved in lignin metabolism within the phenylpropanoid pathway. Here, we screened 26 OMT genes from the Pyrus bretschneideri cv. Dangshan Su genome using the DNATOOLs software. To characterize the OMT ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…Factors such as the size, content and density of stone cells in pear are thought to greatly affect pear quality ( Jin et al, 2013 ; Cheng et al, 2016 ). It has been shown that the lignin content of mature stone cells is approximately 18% ( Lee et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as the size, content and density of stone cells in pear are thought to greatly affect pear quality ( Jin et al, 2013 ; Cheng et al, 2016 ). It has been shown that the lignin content of mature stone cells is approximately 18% ( Lee et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dangshan Su is a pear variety originating in China that is known for its fruit, which bears a wealth of nutritional and medicinal value. ‘Dangshan Su’ has relatively high stone cell content in the fruit, which is a crucial factor influencing the quality of pear fruit by affecting not only sucrose and other nutrient contents but also flesh hardness and chewiness [ 1 , 2 ]. The ‘Lianglizaosu’ variety originated from a natural bud sport of ‘Dangshan Su’ pear.…”
Section: Introductionmentioning
confidence: 99%
“…Stone cells are widely present in various parts of fruit, especially in the flesh, which reduces the quality of fruit [34][35][36] . Recent studies have focused on the cloning and regulation of lignin synthesis structural genes based on the pear genome and germplasm resources 37,38 .…”
Section: Discussionmentioning
confidence: 99%